Analisis Peranan Sumber Daya Manusia Dalam Pencapaian Kinerja Perusahaan pada PT. Perusahaan Perdagangan Indonesia (Persero) Regional Medan - Aswardi, Aswardi; Lubis, Yusniar; Lubis, Syaifuddin (Universitas Medan Area, 2019)
The aims of study to identify and analyze the role of human resources (individual characteristics, quality, and employee competence) on the company's performance at Indonesia Trading Company of Medan Regional. This research using a quantitative approach with survey on the type of research. The sample was determined by simple random sampling method, 51 people. The data collection through questionnaires. Data were analyzed using multiple linear regression. The research results shows that simultaneously, the variable of individual characteristics, employee quality and employee competence have a positive and significantly effect to the performance at Indonesia Trading Company of Medan Regional. The determination coefficient value of 0.616 indicates that the influence of individual characteristics, employee quality and employee competence on the change of company performance at Indonesia Trading Company of Medan Regional is 61.6%. Partially, there are positive and significantly influence of employee quality and employee competence to company performance at Indonesia Trading Company of Medan Regional. While the variable of employee characteristic have a non significantly effect to company performance Indonesia Trading Company of Medan Regional.